Writing Direction Affects How People Map Space Onto Time - Bergen, Benjamin; Chan Lau, Ting Ting (Frontiers in Psychology, 2012)
What determines which spatial axis people use to represent time? We investigate effects of writing direction. English, like Mandarin Chinese in mainland China, is written left-to-right and then top-to-bottom. But in Taiwan, characters are written predominantly top-to-bottom and then right-to-left. Because being a fluent reader-writer entails thousands of hours of experience with eye and hand movement in the direction dictated by one's writing system, it could be that writing system direction affects the axis used to represent time in terms of space. In a behavioral experiment, we had native speakers of English, Mandarin Chinese from mainland China, and Mandarin Chinese from Taiwan place sets of cards in temporal order. These cards depicted stages of development of plants and animals, for instance: tadpole, froglet, frog. Results showed that English speakers always represented time as moving from left to right. Mainland Chinese participants trended in the same direction, but a small portion laid the cards out from top to bottom. Taiwanese participants were just as likely to depict time as moving from left to right as from top to bottom, with a large minority depicting it as moving from right to left. Native writing system affects how people represent time spatially.